2018
DOI: 10.3390/electronics7070101
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Enhanced Imaging Method on Human Body for Ultra-Wideband Multiple-Input Multiple-Output Radar

Abstract: High-resolution three-dimensional (3D) images can be acquired by the planar Multiple-Input Multiple-Output (MIMO) array radar making future work like detection and tracking easier. However, regarding portability and to save the costs of radar system, MIMO radar array adopts sparse type with limited number of antennas, so the imaging performance of a MIMO radar system is limited. In this paper, the 3D back projection imaging algorithm is verified by the experimental results of planar MIMO array for human body a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It gets well utilized in many fields, such as radar, medical diagnosis, sources location, etc. [2], [3]. It's evident that much work has been done on DOA estimation, accompanied by a series of corresponding high-resolution estimation algorithms [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It gets well utilized in many fields, such as radar, medical diagnosis, sources location, etc. [2], [3]. It's evident that much work has been done on DOA estimation, accompanied by a series of corresponding high-resolution estimation algorithms [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…As the l-th sub-block of Uθ 1w and Uθ 2w , Uθ l 1w and Uθ l 2w are equal to the (Fl − F + 1)th to (Fl)th rows of Uθ 1w and Uθ 2w , respectively. Then, two new column vectors are introduced for conveniently expressing, that are t 1 = [tθ1 1 , tθ2 1 , . .…”
mentioning
confidence: 99%
“…Antenna arrays are one of the most important technologies that allows responding to the challenges of the close future communication systems, particularly in the 5G and IoT frameworks [1][2][3][4]. In this perspective, the use of sparse, non-regular, arrays is particularly appealing, since it has been shown that a sparse array is often capable of achieving the same performance of regular lattice ones, with a much lower number of radiating elements, and a strong reduction of the issue of grating lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, inspired by the development of multiple-input multiple-output (MIMO) communication technology, MIMO radar has recently been proposed to obtain more degrees of freedom and high resolution for DOA estimation [4]. It has become a hot spot in the fields of autopilot, target location, and medicine [5][6][7]. One problem we must consider is that with a fixed array size, as the number of antennas is increased (or the distance between array elements is decreased), this inevitably brings about mutual coupling effect in the received data.…”
Section: Introductionmentioning
confidence: 99%